Anti-hyperuricemic and Anti-inflammatory Effects of Marantodes pumilum as Potential Treatment for Gout - Rahmi, Eldiza Puji; Kumolosasi, Endang; Jalil, Juriyati; Husain, Khairana; Buang, Fhataheya; Abd. Razak, Amirul Faiz; Jamal, Jamia Azdina (Frontiers in Pharmacology, 2020)
Marantodes pumilum (Primulaceae) has been used in Malaysian folk medicine to help women regain strength after delivery and for “sickness in the bones”. It was previously revealed that its extracts inhibited xanthine oxidase (XO) activity in vitro. The leaves and roots of M. pumilum var. alata (MPA), var. pumila (MPP), and var. lanceolata (MPL) were individually extracted in ethanol (80%). The anti-hyperuricemic activity was initially assessed by XO inhibition with a spectrophotometric in vitro assay. The most active extract was further investigated on hyperuricemic rat model induced by potassium oxonate to determine serum uric acid levels and liver XO effect. The in vitro anti-inflammatory activity was carried out on MSU crystal-induced pro-inflammatory cytokines (i.e. IL-1α, IL-1β, IL-6, IL-8 and TNF-α) secretion using PBMC and ELISA technique, and PGE2 secretion using radioimmunoassay. The active extract was then investigated on gout-induced inflammation with MSU crystals to determine cytokines and PGE2 secretion levels in the rat synovial fluid. Quantitative analysis using validated HPLC was performed on the extracts to determine presence of flavonoids. The findings revealed that MPP leaves gave the highest inhibitory activity on XO (IC50 130.5 µg/mL) compared to other extracts tested. However, all extracts possessed significantly lower activity compared to allopurinol (IC50 0.13 µg/mL). Oral administration of MPP leaf extract (200 mg/kg) significantly reduced serum uric acid level in hyperuricemic rats to the baseline level and it was as effective as allopurinol (5 mg/kg). The extract also inhibited liver XO activity (25%) compared to allopurinol (45%). In vitro anti-inflammatory assay showed that MPP roots inhibited MSU crystals-induced secretion of IL-1α, IL-1β, IL-8, TNF-α and PGE2 with IC50 values of 36, 25, 38, 18 and 46 µg/mL, respectively. Oral administration of the MPP root extract (200 mg/kg) significantly decreased IL-1α, IL-1β, IL-6, TNF-α and PGE2 levels in rat’s synovial fluid as effective as indomethacin. MPP extracts showed presence of myricetin, quercetin and kaempferol. Myricetin was detected with values of 0.2 and 0.6 mg/g for root and leaf extracts, respectively. The anti-hyperuricemic of MPP leaf and anti-inflammatory of MPP root indicated that MPP may be promising for complementary therapy of gout.